2022
DOI: 10.1093/oncolo/oyab070
|View full text |Cite
|
Sign up to set email alerts
|

Marital Status, Living Arrangement, and Cancer Recurrence and Survival in Patients with Stage III Colon Cancer: Findings from CALGB 89803 (Alliance)

Abstract: Background Limited and conflicting findings have been reported regarding the association between social support and colorectal cancer (CRC) outcomes. We sought to assess the influences of marital status and living arrangement on survival outcomes among patients with stage III colon cancer. Patients and Methods We conducted a secondary analysis of 1082 patients with stage III colon cancer prospectively followed in the CALGB 89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…In contrast, it has been suggested that younger patients may have a better tolerance to the adverse effects of treatment, including myelosuppression after chemotherapy, compared with that in elderly patients. Additionally, in this study, unmarried patients were more prone to anxiety and had greater stress burdens than married patients, thereby reducing their immune capacity and affecting their metabolic balance, resulting in decreased survival 26,27 . In addition, unmarried patients had poorer compliance with treatment and received the treatment later, which may also be a reason for their poor prognoses 28 …”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In contrast, it has been suggested that younger patients may have a better tolerance to the adverse effects of treatment, including myelosuppression after chemotherapy, compared with that in elderly patients. Additionally, in this study, unmarried patients were more prone to anxiety and had greater stress burdens than married patients, thereby reducing their immune capacity and affecting their metabolic balance, resulting in decreased survival 26,27 . In addition, unmarried patients had poorer compliance with treatment and received the treatment later, which may also be a reason for their poor prognoses 28 …”
Section: Discussionmentioning
confidence: 76%
“…Additionally, in this study, unmarried patients were more prone to anxiety and had greater stress burdens than married patients, thereby reducing their immune capacity and affecting their metabolic balance, resulting in decreased survival. 26,27 In addition, unmarried patients had poorer compliance with treatment and received the treatment later, which may also be a reason for their poor prognoses. 28 Zhu et al observed that White patients had the highest risk of GCA compared with that in the other ethnic groups, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that persons with improved living status and social support have been shown to have a better outcome, decreased mortality, and an increased disease‐free interval. 6 Also, the quality of life is enhanced. Because the environment has a large influence on disease behavior, your living situation may have influenced the disease's recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also finds a strong link between living status and disease recurrence ( p value of 0.01). Studies suggest that persons with improved living status and social support have been shown to have a better outcome, decreased mortality, and an increased disease‐free interval 6 . Also, the quality of life is enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have attempted to quantify relationship changes after cancer diagnosis, and no studies to date have sought to determine whether changes in relationship intimacy in HNSCC are associated with a diagnosis of HPV or the effects of cancer diagnosis and treatment. Multiple studies have demonstrated that relationship quality and satisfaction can affect patient and partner adjustment to cancer and that patients who are divorced or separated tend to have worse oncologic outcomes 17–22 . Therefore, understanding the impact of HNSCC on patient relationships may improve our approach to providing holistic cancer care.…”
Section: Discussionmentioning
confidence: 99%